Controlling armchair and zigzag edges in oxidative cutting of graphene - Sk, Mahasin Alam (2017)
Density-functional theory (DFT) calculations reveal that the formation of an armchair epoxy chain on a graphene sheet is energetically favorable when oxidation occurred on both sides of the graphene sheet. However, the formation of a zigzag epoxy chain is favorable when oxidation occurred on the same side of the graphene sheet. In addition, the zigzag epoxy chain formation on the graphene sheet becomes energetically more favorable when external strain is applied on graphene. Our theoretical calculations show that the edge (armchair or zigzag) of graphene nanoribbons (GNRs) and graphene quantum dots (GQDs) can be synthetically controlled by (a) experimental conditions which allow the oxidation of graphene to occur on either one or both sides of the graphene sheet and (b) engineering the strain on the graphene sheet.